Sustainability development: part 3 - the cybernetics of co-evolution through amenity. (2018) - Yolles, Maurice
This is the third part of a three-part paper. The first part explored the nature of complex autonomous human activity systems, showing that they may be represented as third order cybernetic systems. In part 2 sustainability development was explored as an agency coevolving supersystem composed of interactive autonomous agency systems. In this third part of the paper, five systems are adopted in the supersystem that contributes to sustainability development. The supersystem and systems each have amenities. These change with system evolution. A literature review is undertaken to validate the suggested prime amenity of each system. Cultural Agency Theory (CAT) is used to model both the agencies and their interactive environment, all of which should have a capacity for sustainability. Each agency model has living system characteristics, with eigenvalues that are indicative of system stability, and eigenbehaviour that determines potential patterns of behaviour.